Production and Nutrient Quality of Rice Straw of Local Rice Varieties From South Kalimantan - Ika Sumantri; Sholih Nugroho Hadi (TROPICAL WETLAND JOURNAL, 2019)
A survey and laboratory study was conducted to estimate rice straw production of local rice varieties from South Kalimantan. Two local rice varieties (Siam Adil and Pandak) cultivated in a tidal swamp paddy field in Tanah Laut regency were harvested at the same time to estimate the dry matter production of rice straws and to obtain the rice straws samples. Rice straws samples were analysed to determine the percentage of botanical parts and nutrient contents, including the contents of dry matter, organic matter, crude protein, and crude fiber. Results showed Siam Adil rice straw had a lower percentage of leaf but had higher percentage of stem compare to Pandak. The botanical fraction of Pandak was similar to the improved rice variety (Ciherang). Siam Adil produced higher rice straw dry matter (7.95 tonnes/ha) compare to Pandak (5.83 tonnes/ha). There were no significant differences in the contents of dry matter, crude protein, and crude fibre of both local varieties. However, local rice straws had lower crude protein and higher crude fiber contents compared to the improved rice straw. In conclusion, local rice varieties potentially produced higher rice straw biomass but had lower nutrient quality. Thus, pretreatment is necessary to improve the utilization of local rice straw as a ruminant feed.